Ni nanoparticle-reinforced porous electromagnetic shielding film and preparation method thereof

Through the synergistic effect of Ni nanoparticles and Ti3C2Tx MXene and the impedance matching regulation of the porous structure, a Ni/Ti3C2Tx MXene porous composite film was prepared, which solved the problem of low electromagnetic shielding performance of Ti3C2Tx MXene and achieved efficient electromagnetic shielding effect.

CN119233616BActive Publication Date: 2025-04-08XIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411341373.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-04-08
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing Ti3C2Tx MXene electromagnetic shielding materials have low electromagnetic shielding performance, which is limited by factors such as excessive intrinsic conductivity, poor impedance matching and single loss mechanism.

Method used

Ni/Ti3C2Tx MXene porous composite film was prepared by synergistically acting with Ni nanoparticles and Ti3C2Tx MXene, combined with impedance matching regulation of the porous structure. The method includes preparing PMMA/Ti3C2Tx MXene nanospheres by template method and preparing PMMA@Ni/Ti3C2Tx MXene nanospheres by hydrothermal method, and finally obtaining a porous composite film by vacuum-assisted suction filtration and freeze-drying.

Benefits of technology

The Ti3C2Tx MXene electromagnetic shielding performance is significantly improved, the synergistic effect of impedance matching and magnetic-dielectric loss is achieved, the electromagnetic shielding efficiency is improved, and the process flow is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119233616B_ABST
    Figure CN119233616B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a Ni nanoparticle-enhanced porous electromagnetic shielding film, which specifically comprises the following steps: step 1, PMMA@Ni / Ti 3 C 2 T x Preparation of MXene nanospheres; Step 2, Ni / Ti 3 C 2 T x Preparation of MXene porous composite film. Also disclosed is a Ni nanoparticle-reinforced porous electromagnetic shielding film, which is prepared by combining Ni nanoparticles with Ti 3 C 2 T x The synergistic effect of MXene in performance and the impedance matching regulation of the porous structure solve the problem of single Ti 3 C 2 T x The problem of low electromagnetic shielding performance of MXene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new materials, and in particular relates to a Ni nanoparticle-enhanced porous electromagnetic shielding film, and also relates to a preparation method of the Ni nanoparticle-enhanced porous electromagnetic shielding film. Background Art

[0002] Electromagnetic shielding materials are functional materials that can shield electromagnetic waves to protect electronic devices and equipment. Currently, commercial electromagnetic shielding materials are mainly metals and their alloys, which have problems such as high density, poor corrosion resistance and difficult processing, which limits their application. 3 C 2 T x MXene materials have the characteristics of good conductivity, light weight, large specific surface area and high mechanical strength. Thanks to the rich internal carriers, Ti 3 C 2 T x MXene exhibits metal-like conductivity, which is very beneficial for electromagnetic shielding dominated by dielectric loss. 3 C 2 T x There are a large number of defects and terminal groups on the surface of MXene, which can easily lead to uneven electron distribution. Under the action of an external field, the aggregated electrons will form dipoles, thereby generating polarization loss and attenuating electromagnetic waves.

[0003] However, due to factors such as high intrinsic conductivity, poor impedance matching and single loss mechanism, Ti 3 C 2 T x The electromagnetic shielding performance of MXene is still somewhat far from commercial requirements. Summary of the invention

[0004] The first object of the present invention is to provide a Ni nanoparticle-reinforced porous electromagnetic shielding film, wherein Ni nanoparticles and Ti 3 C 2 T x The synergistic effect of MXene in performance and the impedance matching regulation of the porous structure solve the problem of single Ti 3 C 2 T x The problem of low electromagnetic shielding performance of MXene.

[0005] The second object of the present invention is to provide a method for preparing a Ni nanoparticle-reinforced porous electromagnetic shielding film. The method is simple and easy to operate. The prepared film is prepared by combining Ni nanoparticles with Ti 3 C 2 T xThe synergistic effect of MXene in performance and the impedance matching regulation of the porous structure solve the problem of single Ti 3 C 2 T x The problem of low electromagnetic shielding performance of MXene.

[0006] The first technical solution adopted by the present invention is a method for preparing a Ni nanoparticle-reinforced porous electromagnetic shielding film, which specifically comprises the following steps:

[0007] Step 1, PMMA@Ni / Ti 3 C 2 T x Preparation of MXene nanospheres;

[0008] Step 2, Ni / Ti 3 C 2 T x Preparation of MXene porous composite films.

[0009] The present invention is also characterized in that:

[0010] Step 1 is implemented as follows:

[0011] Step 1.1, preparation of PMMA / Ti by template method 3 C 2 T x MXene nanosphere mixed solution:

[0012] First, a PMMA nanosphere dispersion with a concentration of 10 mg / mL to 20 mg / mL was prepared, and ultrasonic treatment was performed for 1 h to 3 h. Then, a Ti dispersion with a concentration of 2 mg / mL to 4 mg / mL was prepared. 3 C 2 T x MXene nanosheet dispersion; Ti 3 C 2 T x The MXene nanosheet dispersion is slowly dripped into the PMMA nanosphere dispersion, and the PMMA and Ti in the mixed solution 3 C 2 T x The mass ratio of MXene nanosheets is 1:1-2, the mixed solution is ultrasonically treated in an ice bath for 20-40 min, and magnetically stirred for 2-5 h to obtain PMMA / Ti 3 C 2 T x MXene nanosphere mixed solution;

[0013] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti 3 C 2 Tx MXene nanospheres:

[0014] NiCl 2 6H 2 O was dissolved in anhydrous ethanol to prepare a solution with a concentration of 0.6 mg / mL to 4 mg / mL, and ultrasonically treated for 20 min to 40 min to mix evenly. The solution was added dropwise to the PMMA / Ti obtained in step 1.1. 3 C 2 T x After the solution is added, the mixture is stirred for 1 h to 3 h to obtain a mixed solution A. NaOH is added to the mixed solution A, and the concentration of NaOH in the mixed solution A is 0.5 g / mL to 0.8 g / mL. Then, the mixture is stirred in an ice bath for 20 min to 40 min to fully dissolve the mixed solution B. 2 H 4 ·H 2 O was added dropwise to the mixed solution B, N 2 H 4 ·H 2 The volume ratio of O to anhydrous ethanol is 1:1-3, and the mixed solution C is obtained by stirring for 20-40 minutes. The fully stirred mixed solution C is placed in a stainless steel reactor, and then a hydrothermal reaction is carried out in a drying oven at 120°C-150°C for 10-15 hours. After the reaction is completed, the black PMMA@Ni / Ti is obtained by washing and drying. 3 C 2 T x MXene nanosphere powder.

[0015] In step 1.1: the size of PMMA nanospheres is 200nm to 600nm; 3 C 2 T x MXene nanosheets are made of Ti 3 AlC 2 The powder is prepared by chemical etching, and the etchant is HCl / LiF.

[0016] Step 2 is implemented as follows:

[0017] Take the concentration of 2mg / mL~4mg / mL Ti 3 C 2 T x The MXene nanosheet dispersion was filtered for the first layer. After the first layer of water was drained, PMMA@Ni / Ti was prepared according to step 1.2. 3 C 2 T xMXene nanosphere powder was dissolved in deionized water to prepare a dispersion with a concentration of 8 mg / mL to 16 mg / mL, and then 8 mg / mL to 16 mg / mL of PMMA@Ni / Ti 3 C 2 T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer of water was drained, a Ti solution with a concentration of 2 mg / mL to 4 mg / mL was taken. 3 C 2 T x The MXene nanosheet dispersion was filtered for the third layer; the volume ratio of the three-layer filtrate was 1:1 to 4:1. After the water of the entire film was drained, it was taken out with the filter membrane, and then vacuum-freeze-dried for 20h to 28h before being separated from the filter membrane to obtain PMMA@Ni / Ti 3 C 2 T x The MXene film was placed in a quartz boat, put into a tube furnace, and heated to 400°C to 600°C at a heating rate of 2°C / min to 5°C / min. The temperature was kept for 1h to 3h, and the Ni / Ti was obtained after cooling to room temperature with the furnace. 3 C 2 T x MXene porous composite film.

[0018] The second technical solution adopted by the present invention is that the Ni nanoparticle-reinforced porous electromagnetic shielding film is prepared by the above method.

[0019] The beneficial effects of the present invention are:

[0020] (1) The method of the present invention prepares PMMA / Ti by template method 3 C 2 T x MXene nanospheres, and then PMMA@Ni / Ti was prepared by hydrothermal method 3 C 2 T x MXene nanospheres, PMMA@Ni / Ti prepared above 3 C 2 T x MXene nanospheres were introduced into the film material, and Ni / Ti with both porous structure and magnetic-dielectric loss capacity was obtained by heat treatment, vacuum-assisted filtration and freeze drying. 3 C 2 T x MXene porous film. At the same time, the present invention prepares Ni / Ti 3 C 2 T x The method of preparing MXene porous films has the characteristics of simple process flow.

[0021] (2) The method of the present invention solves the problems of high density, poor corrosion resistance and difficult processing of the currently commercial electromagnetic shielding materials mainly composed of metals and their alloys. In addition, by using Ni nanoparticles, Ti 3 C 2 T x The synergistic effect of MXene performance and the hollow structure optimized impedance matching solves the problem of Ti 3 C 2 T x The problem of low electromagnetic shielding performance of MXene.

[0022] (3) The thin film of the present invention is formed by Ti 3 C 2 T x MXene combined with magnetic Ni nanoparticles can give Ti 3 C 2 T x The magnetic loss capacity of MXene materials is combined with the design of porous structures to optimize impedance matching, and the electromagnetic shielding performance is enhanced through the synergistic optimization of performance and structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The Ni / Ti prepared in Example 1 3 C 2 T x MXene porous composite film PMMA@Ni / Ti 3 C 2 T x XRD pattern of MXene nanospheres;

[0024] Figure 2 PMMA@Ni / Ti prepared in Example 1 3 C 2 T x TEM image of MXene nanospheres;

[0025] Figure 3 The Ni / Ti prepared in Example 1 3 C 2 T x SEM image of the cross section of MXene porous composite film;

[0026] Figure 4 for Figure 3 Magnified image of area “A” in the middle;

[0027] Figure 5 Ni / Ti 3 C 2 T xElement distribution image of C element in MXene porous composite film;

[0028] Figure 6 Ni / Ti 3 C 2 T x Element distribution image of Ti element in MXene porous composite film;

[0029] Figure 7 Ni / Ti 3 C 2 T x Element distribution image of Ni element in MXene porous composite film. DETAILED DESCRIPTION

[0030] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0031] The present invention provides a method for preparing a Ni nanoparticle-reinforced porous electromagnetic shielding film, which specifically comprises the following steps:

[0032] Step 1, PMMA@Ni / Ti 3 C 2 T x Preparation of MXene nanospheres;

[0033] Step 1 is implemented as follows:

[0034] Step 1.1, preparation of PMMA / Ti by template method 3 C 2 T x MXene nanosphere mixed solution:

[0035] First, a PMMA nanosphere dispersion with a concentration of 10 mg / mL to 20 mg / mL was prepared, and ultrasonic treatment was performed for 1 h to 3 h. Then, a Ti dispersion with a concentration of 2 mg / mL to 4 mg / mL was prepared. 3 C 2 T x MXene nanosheet dispersion; Ti 3 C 2 T x The MXene nanosheet dispersion is slowly dripped into the PMMA nanosphere dispersion, and the PMMA and Ti in the mixed solution 3 C 2 T x The mass ratio of MXene nanosheets is 1:1-2, the mixed solution is ultrasonically treated in an ice bath for 20-40 min, and magnetically stirred for 2-5 h to obtain PMMA / Ti 3 C 2 T x MXene nanosphere mixed solution;

[0036] In step 1.1: the size of PMMA nanospheres is 200nm to 600nm; 3 C 2 T x MXene nanosheets are made of Ti 3 AlC 2 The powder is prepared by chemical etching, and the etchant is HCl / LiF.

[0037] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti 3 C 2 T x MXene nanospheres:

[0038] NiCl 2 6H 2 O was dissolved in anhydrous ethanol to prepare a solution with a concentration of 0.6 mg / mL to 4 mg / mL, and ultrasonically treated for 20 min to 40 min to mix evenly. The solution was added dropwise to the PMMA / Ti obtained in step 1.1. 3 C 2 T x After the solution is added, the mixture is stirred for 1 h to 3 h to obtain a mixed solution A. NaOH is added to the mixed solution A, and the concentration of NaOH in the mixed solution A is 0.5 g / mL to 0.8 g / mL. Then, the mixture is stirred in an ice bath for 20 min to 40 min to fully dissolve the mixed solution B. 2 H 4 ·H 2 O is quickly added dropwise to the mixed solution B, N 2 H 4 ·H 2 The volume ratio of O to anhydrous ethanol is 1:1-3, and the mixed solution C is obtained by stirring for 20-40 minutes. The fully stirred mixed solution C is placed in a stainless steel reactor, and then a hydrothermal reaction is carried out in a drying oven at 120°C-150°C for 10-15 hours. After the reaction is completed, the black PMMA@Ni / Ti is obtained by washing and drying. 3 C 2 T x MXene nanosphere powder.

[0039] Step 2, Ni / Ti 3 C 2 T x Preparation of MXene porous composite films;

[0040] Step 2 is implemented as follows:

[0041] Take the concentration of 2mg / mL~4mg / mL Ti3 C 2 T x The MXene nanosheet dispersion was filtered for the first layer. After the first layer of film was dried, PMMA@Ni / Ti was prepared according to step 1.2. 3 C 2 T x MXene nanosphere powder was dissolved in deionized water to prepare a dispersion with a concentration of 8 mg / mL to 16 mg / mL, and then 8 mg / mL to 16 mg / mL of PMMA@Ni / Ti 3 C 2 T x The MXene nanosphere dispersion was filtered through the second membrane. After the second layer of water was drained, the Ti solution with a concentration of 2 mg / mL to 4 mg / mL was taken. 3 C 2 T x The MXene nanosheet dispersion was filtered for the third layer; the volume ratio of the three-layer filtrate was 1:1 to 4:1. After the water of the entire film was drained, it was taken out with the filter membrane, and then vacuum-freeze-dried for 20h to 28h before being separated from the filter membrane to obtain PMMA@Ni / Ti 3 C 2 T x The MXene film was placed in a quartz boat, put into a tube furnace, and heated to 400°C to 600°C at a heating rate of 2°C / min to 5°C / min. The temperature was kept for 1h to 3h, and the Ni / Ti was obtained after cooling to room temperature with the furnace. 3 C 2 T x MXene porous composite film.

[0042] The present invention also provides a Ni nanoparticle-reinforced porous electromagnetic shielding film, which is prepared by the above method.

[0043] Example 1

[0044] Ni nanoparticles reinforced Ti 3 C 2 T x The preparation method of the MXene porous electromagnetic shielding film specifically comprises the following steps:

[0045] Step 1, PMMA@Ni / Ti 3 C 2 T x Preparation of MXene nanospheres;

[0046] Step 1 is implemented as follows:

[0047] Step 1.1, Preparation of PMMA / Ti 3 C 2 Tx MXene nanosphere mixed solution:

[0048] PMMA nanospheres were dispersed in deionized water to prepare a 10 mg / mL dispersion and ultrasonically treated for 1 h.

[0049] Etching Ti using HCl / LiF 3 AlC 2 Powders, HCl, LiF and Ti 3 AlC 2 The mass ratio is 30:2:1. The three are mixed and stirred in a constant temperature water bath for 24 hours. Finally, they are centrifuged and washed with deionized water until the solution pH is 6, thus obtaining Ti 3 C 2 T x MXene nanosheet dispersion.

[0050] Ti 3 C 2 T x After the MXene nanosheet dispersion was diluted to 2 mg / mL, 10 mL of the solution was taken into a beaker and 2 mL of 10 mg / mL PMMA nanosphere dispersion was slowly dripped into it. The mixture was ultrasonically treated in an ice bath for 20 min and magnetically stirred for 2 h to obtain PMMA / TiO2. 3 C 2 T x MXene nanosphere mixed solution.

[0051] In step 1.1, the size of the PMMA beads is 350 nm.

[0052] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti 3 C 2 T x MXene nanospheres:

[0053] Weigh 0.02g NiCl 2 6H 2 O was dissolved in 10 mL of anhydrous ethanol, ultrasonically treated for 20 min to mix evenly, and the solution was added dropwise to the PMMA / Ti obtained in step 1.1. 3 C 2 T x After the solution was added, the mixture was stirred for 1 h to obtain a mixed solution A. 5 g of NaOH was weighed and added to the mixed solution A, and then stirred in an ice bath for 20 min to fully dissolve it to obtain a mixed solution B. Then 10 mL of N 2 H 4 ·H 2O was quickly added dropwise to the mixed solution B and stirred for 20 min to obtain a mixed solution C. The fully stirred mixed solution C was placed in a stainless steel reactor and then subjected to a hydrothermal reaction in a drying oven at 120 °C for 10 h. After the reaction was completed, the black PMMA@Ni / Ti was obtained by washing and drying. 3 C 2 T x MXene nanosphere powder.

[0054] Step 2, Ni / Ti 3 C 2 T x Preparation of MXene porous composite films.

[0055] Step 2 is implemented as follows:

[0056] Take 2mL of 2mg / mL Ti 3 C 2 T x The MXene nanosheet dispersion was filtered for the first layer. After the first layer of water was drained, the PMMA@Ni / Ti prepared in step 1.2 was added. 3 C 2 T x MXene nanosphere powder was dissolved in deionized water to prepare a dispersion of 8 mg / mL, and then 5 mL of PMMA@Ni / Ti 3 C 2 T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer was drained, 2 mL of 2 mg / mL nanosheet dispersion was taken for the third layer. After the entire film was drained, it was taken out with the filter membrane, and after vacuum freeze drying for 20 hours, PMMA@Ni / Ti was obtained by separating from the filter membrane. 3 C 2 T x MXene film. Place it in a quartz boat and put it into a tube furnace with Ar gas protection. Heat it to 400℃ at a heating rate of 2℃ / min and keep it warm for 1h. Cool it to room temperature and take it out to obtain Ni / Ti 3 C 2 T x MXene porous composite film.

[0057] Parameter 1: The diameter of the filtration membrane prepared in step 2 of Example 1 is 40 mm, and the filter membrane is a water-based mixed cellulose membrane with a pore size of 0.4 μm;

[0058] Parameter 2: Ni / Ti prepared in step 2 of Example 1 3 C 2 T x The maximum electrical conductivity of the MXene porous composite film is 234.8S / m;

[0059] Parameter 3: Ni / Ti prepared in step 2 of Example 1 3 C 2 T x The saturation magnetization Ms and coercive force Hc of the MXene porous composite film are 13.69emu / g and 77.38Oe, respectively;

[0060] Parameter 4: Ni / Ti prepared in step 2 of Example 1 3 C 2 T x The electromagnetic shielding effectiveness of MXene porous composite film is 70.7dB.

[0061] Figure 1 The Ni / Ti prepared in Example 1 3 C 2 T x MXene porous film and PMMA@Ni / Ti 3 C 2 T x XRD spectrum of MXene nanospheres. From the figure, it can be found that both samples have diffraction peaks at 44.3°, 51.7° and 76.1°, which are consistent with the standard PDF card of Ni (PDF#89-7128), corresponding to the (111), (200) and (220) crystal planes respectively. 3 C 2 T x The X-ray diffraction peak intensity of the MXene porous composite film is enhanced and the half-peak width is narrowed, indicating that the crystallinity of the Ni grains is improved. 3 C 2 T x The 2θ angle of the (002) crystal plane diffraction peak of MXene shifts to the left to 6.9°, indicating that the embedding of some Ni atoms increases the Ti 3 C 2 T x The interplanar spacing of MXene. No other peaks appear, indicating that 3 C 2 T x High-purity elemental Ni was successfully synthesized on MXene hollow nanospheres.

[0062] Figure 2 PMMA@Ni / Ti prepared in Example 1 3 C 2 T x TEM image of MXene nanospheres. It can be seen from the figure that the nanospheres have a stable structure and a size of about 350nm.

[0063] Figure 3 The Ni / Ti prepared in Example 1 3 C 2 T x SEM image of the cross section of the MXene porous composite film. As can be seen from the figure, the film thickness is about 20 microns, the layers are tightly bonded, and the middle is a typical hollow sphere structure.

[0064] Figure 4 for Figure 3 The enlarged image of the "A" area in the figure shows that the center of the composite film is a typical hollow sphere porous structure.

[0065] Figure 5 , Figure 6 , Figure 7 Ni / Ti 3 C 2 T x The element distribution images of C, Ti and Ni elements in the MXene porous composite film show that the three elements are evenly distributed.

[0066] Example 2

[0067] Ni nanoparticles reinforced Ti 3 C 2 T x The preparation method of the MXene porous electromagnetic shielding film specifically comprises the following steps:

[0068] Step 1, PMMA@Ni / Ti 3 C 2 T x Preparation of MXene nanospheres;

[0069] Step 1 is implemented as follows:

[0070] Step 1.1, preparation of PMMA@Ti by template method 3 C 2 T x MXene nanosphere mixed solution:

[0071] PMMA nanospheres were prepared into a 12 mg / mL dispersion and ultrasonically treated for 1.5 h.

[0072] Etching Ti using HCl / LiF 3 AlC 2 Powder. HCl, LiF and Ti 3 AlC 2 The mass ratio is 30:2:1. After mixing the three, stir in a constant temperature water bath for 24 hours, and finally centrifuge and wash with deionized water until the solution pH is 6, thus obtaining Ti 3 C2 T x MXene nanosheet dispersion.

[0073] After the nanosheet dispersion was diluted to 2.5 mg / mL, 2 mL of 12 mg / mL PMMA nanosphere dispersion was slowly dripped into 10 mL of the solution. The mixture was ultrasonically treated in an ice bath for 25 min and magnetically stirred for 3 h to obtain PMMA@Ti 3 C 2 T x MXene nanosphere mixed solution.

[0074] In step 1.1, the size of the PMMA beads is 300 nm.

[0075] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti 3 C 2 T x MXene nanospheres:

[0076] Weigh 0.03g NiCl 2 6H 2 O was dissolved in 15 mL of anhydrous ethanol and ultrasonically treated for 25 min to mix well. The solution was added dropwise to the PMMA / Ti obtained in step 1.1. 3 C 2 T x After the solution was added, the mixture was stirred for 1.5 h to obtain a mixed solution A. 6 g of NaOH was weighed and added to the mixed solution A, and then stirred in an ice bath for 25 min to fully dissolve it to obtain a mixed solution B. Then 15 mL of NaOH was weighed and added to the mixed solution A. 2 H 4 ·H 2 O was quickly added dropwise to the mixed solution B, and stirred for 25 min to obtain a mixed solution C. The fully stirred mixed solution C was placed in a stainless steel reactor, and then subjected to a hydrothermal reaction in a drying oven at 130 °C for 11 h. After the reaction was completed, the black PMMA@Ni / Ti was obtained by washing and drying. 3 C 2 T x MXene nanosphere powder.

[0077] Step 2, Ni / Ti 3 C 2 T x Preparation of MXene porous composite films;

[0078] Step 2 is implemented as follows:

[0079] Take 2.5mL of 2.5mg / mLTi 3 C 2 Tx The MXene nanosheet dispersion was filtered for the first layer. After the first layer of water was drained, PMMA@Ni / Ti was prepared according to step 1.2. 3 C 2 T x MXene nanosphere powder was dissolved in deionized water to prepare a 9 mg / mL dispersion, and then 5 mL of PMMA@Ni / Ti 3 C 2 T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer was drained, 2.5 mL of 2.5 mg / mL nanosheet dispersion was taken for the third layer. After the entire film was drained, it was taken out with the filter membrane, and after vacuum freeze drying for 22 hours, it was separated from the filter membrane to obtain PMMA@Ni / Ti 3 C 2 T x MXene film. Place it in a quartz boat, put it into a tube furnace, and pass Ar gas protection. Heat it to 500℃ at a heating rate of 3℃ / min and keep it warm for 1.5h. After cooling to room temperature in the furnace, Ni / Ti 3 C 2 T x MXene porous composite film.

[0080] Example 3

[0081] Ni nanoparticles reinforced Ti 3 C 2 T x The preparation method of the MXene porous electromagnetic shielding film specifically comprises the following steps:

[0082] Step 1, PMMA@Ni / Ti 3 C 2 T x Preparation of MXene nanospheres;

[0083] Step 1 is implemented as follows:

[0084] Step 1.1, preparation of PMMA / Ti by template method 3 C 2 T x MXene nanosphere mixed solution:

[0085] PMMA nanospheres were prepared into a 14 mg / mL dispersion and ultrasonically treated for 2 h.

[0086] Etching Ti using HCl / LiF 3 AlC 2 Powders, HCl, LiF and Ti 3 AlC 2The mass ratio is 30:2:1. After mixing the three, stir in a constant temperature water bath for 24 hours, and finally centrifuge and wash with deionized water until the solution pH is 6, thus obtaining Ti 3 C 2 T x MXene nanosheet dispersion.

[0087] After the nanosheet dispersion was diluted to 3 mg / mL, 2 mL of 14 mg / mL PMMA nanosphere dispersion was slowly dripped into 10 mL of the solution. The mixture was ultrasonically treated in an ice bath for 25 min and magnetically stirred for 4 h to obtain PMMA@Ti 3 C 2 T x MXene nanospheres mixed solution.

[0088] In step 1.1, the size of the PMMA beads is 400 nm.

[0089] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti 3 C 2 T x MXene nanospheres:

[0090] Weigh 0.04g NiCl 2 6H 2 O was dissolved in 20 mL of anhydrous ethanol, ultrasonically treated for 30 min to mix evenly, and the solution was added dropwise to the PMMA / Ti obtained in step 1.1. 3 C 2 T x After the solution was added, the mixture was stirred for 2 h to obtain a mixed solution A. 7 g of NaOH was weighed and added to the mixed solution A, and then stirred in an ice bath for 30 min to fully dissolve it to obtain a mixed solution B. 20 mL of NaOH was weighed and added to the mixed solution A. 2 H 4 ·H 2 O was quickly added dropwise to the mixed solution B and stirred for 30 min to obtain a mixed solution C. The fully stirred mixed solution C was placed in a stainless steel reactor and then subjected to a hydrothermal reaction in a drying oven at 140 °C for 12 h. After the reaction was completed, the black PMMA@Ni / Ti was obtained by washing and drying. 3 C 2 T x MXene nanosphere powder.

[0091] Step 2, Ni / Ti 3 C 2 T x Preparation of MXene porous composite films.

[0092] Step 2 is implemented as follows:

[0093] Take 3mL of 3mg / mLTi 3 C 2 T x The MXene nanosheet dispersion was filtered for the first layer. After the first layer of water was drained, PMMA@Ni / Ti was prepared according to step 1.2. 3 C 2 T x MXene nanosphere powder was dissolved in deionized water to prepare a 9 mg / mL dispersion, and then 6 mL of PMMA@Ni / Ti 3 C 2 T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer was drained, 3 mL of 3 mg / mL nanosheet dispersion was taken for the third layer. After the entire film was drained, it was taken out with the filter membrane, and then vacuum-freeze-dried for 24 hours and then separated from the filter membrane to obtain PMMA@Ni / Ti 3 C 2 T x MXene film. Place it in a quartz boat and put it into a tube furnace with Ar gas protection. Heat it to 500℃ at a heating rate of 4℃ / min and keep it warm for 2h. After cooling to room temperature, Ni / Ti 3 C 2 T x MXene porous composite film.

[0094] Example 4

[0095] Ni nanoparticles reinforced Ti 3 C 2 T x The preparation method of the MXene porous electromagnetic shielding film specifically comprises the following steps:

[0096] Step 1, PMMA@Ni / Ti 3 C 2 T x Preparation of MXene nanospheres;

[0097] Step 1 is implemented as follows:

[0098] Step 1.1, preparation of PMMA / Ti by template method 3 C 2 T x MXene nanosphere mixed solution:

[0099] PMMA nanospheres were prepared into a 16 mg / mL dispersion and ultrasonically treated for 2.5 h.

[0100] Etching Ti using HCl / LiF 3 AlC 2Powder. HCl, LiF and Ti 3 AlC 2 The mass ratio is 30:2:1. After mixing the three, stir in a constant temperature water bath for 24 hours, and finally wash with deionized water until the solution pH = 6, thus obtaining Ti 3 C 2 T x MXene nanosphere dispersion.

[0101] Ti 3 C 2 T x After the MXene nanosheet dispersion was diluted to 3.5 mg / mL, 2 mL of 16 mg / mL PMMA nanosphere dispersion was slowly dripped into 10 mL of the solution. The mixture was ultrasonically treated in an ice bath for 35 min and magnetically stirred for 5 h to obtain PMMA@Ti 3 C 2 T x MXene nanosphere mixed dispersion.

[0102] In step 1.1, the size of the PMMA beads is 500 nm.

[0103] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti 3 C 2 T x MXene nanospheres:

[0104] Weigh 0.04g NiCl 2 6H 2 O was dissolved in 25 mL of anhydrous ethanol, ultrasonically treated for 35 min to mix evenly, and the solution was added dropwise to the PMMA / Ti obtained in step 1.1. 3 C 2 T x After the solution was added, the mixture was stirred for 2.5 h to obtain a mixed solution A. 8 g of NaOH was weighed and added to the mixed solution A, and then stirred in an ice bath for 35 min to fully dissolve it to obtain a mixed solution B. Then 25 mL of N 2 H 4 ·H 2 O was quickly added dropwise to the mixed solution B and stirred for 35 min to obtain a mixed solution C. The fully stirred mixed solution C was placed in a stainless steel reactor and then subjected to a hydrothermal reaction in a drying oven at 150 °C for 13 h. After the reaction was completed, the black PMMA@Ni / Ti was obtained by washing and drying. 3 C 2 T x MXene nanosphere powder.

[0105] Step 2, Ni / Ti 3 C2 T x Preparation of MXene porous composite films.

[0106] Step 2 is implemented as follows:

[0107] Take 3.5mL of 3.5mg / mL Ti 3 C 2 T x The MXene nanosheet dispersion was filtered for the first layer. After the first layer of water was drained, PMMA@Ni / Ti was prepared according to step 1.2. 3 C 2 T x MXene nanosphere powder was dissolved in deionized water to prepare a 10 mg / mL dispersion. Then 5 mL of PMMA@Ni / Ti 3 C 2 T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer was drained, 3.5 mL of 3.5 mg / mL nanosheet dispersion was taken for the third layer. After the entire film was drained, it was taken out with the filter membrane, and after vacuum freeze drying for 26 hours, it was separated from the filter membrane to obtain PMMA@Ni / Ti 3 C 2 T x MXene film. Place it in a quartz boat, put it into a tube furnace, and pass Ar gas protection. Heat it to 550℃ at a heating rate of 5℃ / min and keep it warm for 2.5h. After cooling to room temperature in the furnace, Ni / Ti 3 C 2 T x MXene porous composite film.

[0108] Example 5

[0109] Ni nanoparticles reinforced Ti 3 C 2 T x The preparation method of the MXene porous electromagnetic shielding film specifically comprises the following steps:

[0110] Step 1, PMMA@Ni / Ti 3 C 2 T x Preparation of MXene nanospheres;

[0111] Step 1 is implemented as follows:

[0112] Step 1.1, preparation of PMMA / Ti by template method 3 C 2 T x MXene nanosphere mixed solution:

[0113] PMMA nanospheres were prepared into a dispersion of 18 mg / mL and ultrasonically treated for 3 h.

[0114] Etching Ti using HCl / LiF 3 AlC 2 Powder. HCl, LiF and Ti 3 AlC 2 The mass ratio is 30:2:1. After mixing the three, stir in a constant temperature water bath for 24 hours, and finally centrifuge and wash with deionized water until the solution pH is 6, thus obtaining Ti 3 C 2 T x MXene nanosheet dispersion.

[0115] Ti 3 C 2 T x After the MXene nanosheet dispersion was diluted to 4 mg / mL, 2 mL of 20 mg / mL PMMA nanosphere dispersion was slowly dripped into 10 mL of the solution. The mixture was ultrasonically treated in an ice bath for 40 min and magnetically stirred for 5 h to obtain PMMA@Ti 3 C 2 T x MXene nanosphere mixed dispersion.

[0116] In step 1.1, the size of the PMMA beads is 600 nm.

[0117] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti 3 C 2 T x MXene nanospheres:

[0118] Weigh 0.04g NiCl 2 6H 2 O was dissolved in 30 mL of anhydrous ethanol, ultrasonically treated for 40 min to mix evenly, and the solution was added dropwise to the PMMA / Ti obtained in step 1.1. 3 C 2 T x After the solution was added, the mixture was stirred for 3 h to obtain a mixed solution A. 8 g of NaOH was weighed and added to the mixed solution A, and then stirred in an ice bath for 40 min to fully dissolve it to obtain a mixed solution B. Then 30 mL of N 2 H 4 ·H 2O was quickly added dropwise to the mixed solution B, and stirred for 40 min to obtain a mixed solution C. The fully stirred mixed solution C was placed in a stainless steel reactor, and then subjected to a hydrothermal reaction in a drying oven at 150 °C for 15 h. After the reaction was completed, the black PMMA@Ni / Ti was obtained by washing and drying. 3 C 2 T x MXene nanosphere powder.

[0119] Step 2, Ni / Ti 3 C 2 T x Preparation of MXene porous composite films.

[0120] Step 2 is implemented as follows:

[0121] Take 4 mL of 4 mg / mL nanosheet dispersion for the first layer of suction filtration. After the first layer of water is drained, the PMMA@Ni / Ti prepared in step 1.2 is 3 C 2 T x MXene nanosphere powder was dissolved in deionized water to prepare a dispersion of 8 mg / mL, and then 8 mL of PMMA@Ni / Ti 3 C 2 T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer was drained, 4 mL of 4 mg / mL nanosheet dispersion was taken for the third layer. After the entire film was drained, it was taken out with the filter membrane, and after vacuum freeze drying for 28 hours, PMMA@Ni / Ti was obtained by separating from the filter membrane. 3 C 2 T x MXene film. Place it in a quartz boat, put it into a tube furnace, and pass Ar gas protection. Heat it to 600℃ at a heating rate of 5℃ / min and keep it warm for 3h. Cool it to room temperature and take it out to obtain Ni / Ti 3 C 2 T x MXene porous composite film.

[0122] After measurement and analysis, Ti with multiple interface structures and two-component systems was successfully prepared. 3 C 2 T x MXene-based composite materials; After measurement and analysis, each embodiment successfully prepared Ni / Ti with Ni nanoparticles as the reinforcing phase in the porous film 3 C 2 T x MXene composite films.

[0123] The electromagnetic parameters of the composite material in the X-band (8.2-12.4 GHz) were measured using a network vector analyzer, and the total electromagnetic shielding effectiveness was calculated. The results are shown in Table 1. The conductivity data of the corresponding materials are also recorded in Table 1.

[0124] Table 1

[0125] Total electromagnetic shielding effectiveness (dB) Conductivity (S / m) Example 1 70.7 234.8 Example 2 73.2 245.7 Example 3 75.9 259.1 Example 4 76.6 270.2 Example 5 77.4 320.5 <![CDATA[Ti 3 C 2 T x MXene film]]> 32.21 178.3

[0126] The present invention uses porous Ti 3 C 2 T x Ni / Ti was prepared with MXene as the matrix and Ni nanoparticles as the reinforcement. 3 C 2 T x MXene porous composite film. Ni nanoparticles and Ti 3 C 2 T x The synergistic effect of MXene performance and the optimization of impedance matching by porous structure have achieved the goal of Ti 3 C 2 T x Enhanced electromagnetic shielding properties of MXene.

[0127] The method of the present invention can be carried out by Ti 3 C 2 T x The synergistic effect of MXene dielectric loss and Ni nanoparticle magnetic loss, as well as the impedance matching optimization caused by the porous structure, results in a Ni / Ti with high electromagnetic shielding effectiveness. 3 C 2 T x MXene porous composite film. It can be seen from Table 1 that the composite film of the present invention has excellent electromagnetic shielding performance, which is far higher than the performance requirements of commercial electromagnetic shielding materials. 3 C 2 T x The magnetism and electrical conductivity of MXene are also significantly improved compared to the composite film of the present invention.

[0128] When the electromagnetic shielding capability is improved, the conductivity of this system can reach 234.8 to 320.5 (S / m). 3 C 2 T x The method of MXene electromagnetic shielding composite material has the characteristics of simple manufacturing process and good stability. The thickness of the prepared porous composite film is between 20 and 60 μm, and the electromagnetic shielding efficiency in the X-band can reach up to 70.7 dB to 77.4 dB.

Claims

1. A method for preparing a Ni nanoparticle-reinforced porous electromagnetic shielding film, characterized in that: The specific steps include: Step 1, PMMA@Ni / Ti3C2T x Preparation of MXene nanospheres; Step 1 is implemented as follows: Step 1.1, preparation of PMMA / Ti3C2T by template method x MXene nanosphere mixed solution: First, a PMMA nanosphere dispersion with a concentration of 10 mg / mL to 20 mg / mL was prepared and ultrasonically treated for 1 h to 3 h. Then, a Ti3C2T x MXene nanosheet dispersion; Ti3C2T x The MXene nanosheet dispersion was slowly dripped into the PMMA nanosphere dispersion. PMMA and Ti3C2T in the mixed solution x The mass ratio of MXene nanosheets was 1:1~2, and the mixed solution was ultrasonically treated in an ice bath for 20min~40min and magnetically stirred for 2h~5h to obtain PMMA / Ti3C2T x MXene nanosphere mixed solution; In step 1.1: the size of PMMA nanospheres is 200nm~600nm; Ti3C2T x MXene nanosheets were prepared from Ti3AlC2 powder by chemical etching, and the etchant was HCl / LiF; Step 1.2, hydrothermal preparation of PMMA@Ni / Ti3C2T x MXene nanospheres: Dissolve NiCl2·6H2O in anhydrous ethanol to prepare a solution with a concentration of 0.6 mg / mL~4 mg / mL, treat with ultrasound for 20 min~40 min to mix evenly, and then drop the solution into the PMMA / Ti3C2T x In the MXene nanosheet mixed solution, after the solution is added, continue to stir for 1h~3h to obtain a mixed solution A, add NaOH to the mixed solution A, the concentration of NaOH in the mixed solution A is 0.5g / mL~0.8g / mL, and then stir in an ice bath for 20min~40min to fully dissolve it to obtain a mixed solution B; then add N2H4·H2O dropwise to the mixed solution B, the volume ratio of N2H4·H2O to anhydrous ethanol is 1:1~3, stir for 20min~40min to obtain a mixed solution C, put the fully stirred mixed solution C into a stainless steel reactor, and then carry out a hydrothermal reaction in a drying oven at 120℃~150℃ for 10h~15h. After the reaction is completed, wash and dry to obtain PMMA@Ni / Ti3C2T x MXene nanosphere powder; Step 2, Ni / Ti3C2T x Preparation of MXene porous composite films; Step 2 is implemented as follows: Take the concentration of 2 mg / mL~4 mg / mL Ti3C2T x The MXene nanosheet dispersion was filtered for the first layer. After the first layer of water was drained, PMMA@Ni / Ti3C2T was prepared according to step 1.

2. x MXene nanosphere powder was dissolved in deionized water to prepare a dispersion with a concentration of 8 mg / mL~16 mg / mL, and then 8 mg / mL~16 mg / mL of PMMA@Ni / Ti3C2T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer of water was drained, the Ti3C2T x The MXene nanosheet dispersion was filtered for the third layer; the volume ratio of the three-layer filtrate was 1:1~4:1, and the entire film was taken out with the filter membrane after the water was drained, and then separated from the filter membrane after vacuum freeze drying for 20h~28h, and PMMA@Ni / Ti3C2T x The MXene film was placed in a quartz boat, put into a tube furnace, and protected by Ar gas. It was heated to 400 ℃~600 ℃ at a heating rate of 2 ℃ / min~5 ℃ / min, kept at this temperature for 1 h~3 h, and then cooled to room temperature with the furnace to obtain Ni / Ti3C2T x MXene porous composite film.

2. Ni nanoparticle-enhanced porous electromagnetic shielding film, characterized in that: Prepared by the method described in claim 1.

Citation Information

Patent Citations

  • MXene microsphere composite wave-absorbing material modified by spiny Ni elementary substance as well as preparation and application of MXene microsphere composite wave-absorbing material

    CN114390880A